2020
DOI: 10.1111/vco.12655
|View full text |Cite
|
Sign up to set email alerts
|

One‐year conditional survival of dogs and cats with invasive mammary carcinomas: A concept inspired from human breast cancer

Abstract: Numerous studies have described the prognostic factors of canine and feline mammary carcinomas (MCs), that is, variables that predict patient survival after diagnosis. But how does survival estimation evolve in patients that escaped early death from their cancer? In human oncology, conditional survival (CS), the probability of surviving X further years when cancer patients have already survived Y years, is used to analyse cancer outcomes in a long‐term perspective. In this cohort of 344 dogs and 342 cats with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…Invasive breast cancer referred to breast cancer with the ability to invade surrounding tissue, lymph node metastasis, or distant metastasis [18][19][20]. This study investigated the risk factors for axillary lymph node metastasis in patients with invasive breast cancer, and the results suggested that vascular tumor plug and left breast cancer were the risk factors for axillary lymph node metastasis in patients with invasive breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive breast cancer referred to breast cancer with the ability to invade surrounding tissue, lymph node metastasis, or distant metastasis [18][19][20]. This study investigated the risk factors for axillary lymph node metastasis in patients with invasive breast cancer, and the results suggested that vascular tumor plug and left breast cancer were the risk factors for axillary lymph node metastasis in patients with invasive breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, the conditional survival of bitches after mastectomy is proposed to be determined using such significant parameters as lymphatic and vascular invasions, aside from age of patients, stage and histological type of cancer and clinical status. At the same time, research has revealed that long-term prognosis to a greater degree depends on the presence of tumour emboli in lymph and blood vessels (Chocteau et al, 2021). Lymphatic invasion in case of mammary tumours in bitches with developed metastases in regional lymph nodes and remote tissues and the organs is accompanied by significant increase in cancer antigen (СА 15.3) content in blood, which is one of the most significant cancer markers in cases of this pathology (Campos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In dogs and cats with MCs, ER, PR, HER2 and Ki‐67 are not routinely evaluated, but immunophenotypes similar to those described for human BCs (luminal‐A, luminal‐B HER2−, luminal‐B HER2+, HER2‐positive and triple‐negative) have been defined and significantly associated with prognosis: the two most common MC immunophenotypes in dogs and cats are luminal‐B HER2− and triple‐negative cancers, while only luminal‐A MCs are associated with better outcomes (Abadie et al, 2018; Chocteau et al, 2021; Maniscalco et al, 2013; Soares et al, 2016). Currently, such immunophenotypes are not routinely evaluated and have no predictive role, but recent studies demonstrate that HER2‐targeted therapies could be beneficial for cats with HER2‐positive MC (Gameiro, Almeida, et al, 2021; Gameiro, Nascimento, et al, 2021).…”
Section: Influence Of the Type Of Mammary Carcinomas On Treatment Opt...mentioning
confidence: 99%
“…In this group of patients, it is estimated that RT reduced the 15‐year locoregional failure rate from 27% (mastectomy) to 4% (mastectomy + RT), and reduced the mortality rate from 57% to 48% (Overgaard et al, 2007). In dogs and cats with MCs, failure of locoregional control is a major cause of cancer‐related death: in a large study, euthanasia was motivated by inoperable locoregional cancer progression in 13% of dogs (24/181 cancer‐related deaths) and 10% of cats (23/226), and euthanasia was motivated by locoregional relapse that owners were not willing to treat in 20% of dogs (36/181) and 28% of cats (63/226) (Chocteau et al, 2021, supplementary data). Of note, in the same study in both dogs and cats, surgical reintervention after locoregional recurrence was associated with long survival: the median cancer‐specific survival was 44 months in dogs that benefited from second surgery compared to 6 months if locoregional recurrence was untreated, and 25 months in cats with reintervention compared to 11 months without (Chocteau et al, 2021, supplementary data).…”
Section: Locoregional Cancer Control: Surgical Oncology and Radiation...mentioning
confidence: 99%
See 1 more Smart Citation